Review article: Probiotics, prebiotics and dietary approaches during COVID-19 pandemic. (February 2021) - Hu, Jielun; Zhang, Lin; Lin, Winnie; Tang, Whitney; Chan, Francis K.L.; Ng, Siew C.
Abstract: Background: Patients with COVID-19 caused by SARS-CoV-2 exhibit diverse clinical manifestations and severity including enteric involvement. Commensal gut bacteria can contribute to defense against potential pathogens by promoting beneficial immune interactions. Interventions targeting the gut microbiome may have systemic anti-viral effects in SARS-CoV-2 infection. Scope and approach: To summarise alterations of gut microbiota in patients with COVID-19 including impact of specific bacteria on disease severity, discuss current knowledge on the role of probiotics, prebiotics and dietary approaches including vitamin D in preventing and reducing disease susceptibility and review clinical studies using probiotics to target coronavirus. A literature review on SARS-CoV-2, COVID-19, gut microbiome and immunity was undertaken and relevant literature was summarised and critically examined. Key findings and conclusions: Integrity of gut microbiome was perturbed in SARS-CoV-2 infections and associated with disease severity. Poor prognosis in SARS-CoV-2 infection was observed in subjects with underlying co-morbidities who had increased gut permeability and reduced gut microbiome diversity. Dietary microbes, including probiotics or selected prebiotics of Chinese origin, had anti-viral effects against other forms of coronavirus, and could positively impact host immune functions during SARS-CoV-2 infection. Numerous studies are investigating the role of probiotics in preventing and reducing susceptibility to SARS-CoV-2 infection in healthcare workers, household contacts and affected patients. An approach to strengthen intestinal barrier and lower pro-inflammatory states by adopting a more diversified diet during COVID-19 pandemic. SARS-CoV-2 infection is associated with immune dysfunction and gut microbiota alterations. Delineating mechanisms of probiotics, prebiotics and diet with anti-SARS-CoV-2 immunity present opportunities for discovery of microbial therapeutics to prevent and treat COVID-19. Highlights: SARS-CoV-2 infection resulted in immune dysfunction and gut microbiota alterations. Probiotics or prebiotics could improve host immune functions during the infection. Enhance gut barrier by diversified diet was recommended during COVID-19 pandemic.